Using of Multimedia Technologies in the Context of Blended Learning while Teaching a Foreign Language in High School - Stepanyshena, Olena (Pedagogical Discourse, 2022)
The article investigates the use of multimedia technologies in the context of blended learning during foreign language teaching in higher education. The transition to distance learning, due to the pandemic and wartime, has become a serious challenge for all participants in the learning process. The issue of distance education development has become very important. And although distance education is not a substitute for full-time learning and was never planned for the long term, it can be an effective tool not only during quarantine and wartime. In such circumstances, we have to accept this challenge and quickly adapt to new realities. The article presents a concise classification of electronic applications and interactive teaching aids that are convenient to display on the screen of a smartphone, a personal computer or a multimedia board. Particular attention is paid to the use of some of them during distance learning of a foreign language in a professional field. The article investigates the impact of internet and mobile applications on enhancing students’ language skills. It examines the students’ opinion regarding English online learning using various Internet resources. Teaching a foreign language with the using of multimedia technologies makes it possible to move from passive learning to an active form of educational activities, in which the student becomes an active participant. Thus, by increasing the clarity of the material activates the learning process, there is a more productive interaction.